Modeling the mechanism of the vesicular sound generation - Grinchenko, V.T.; Vovk, I.V.; Matsypura, V.T. (Прикладна гідромеханіка, 2016)
Current research presents a mathematical model of the mechanism of vesicular sound generation, based on the assumption of significant contribution of the alveolar walls vibration to generation of noise during the act of respiration. The walls of the alveoli are presented in the form of membranes, and we show that when the membranes are periodically tensed, the transverse oscillations of the membranes occur, causing the sound vibrations in the parenchyma. The characteristics of the composite noise signal, which is formed during the simultaneous excitation of a representative ensemble of membranes with different geometric and mechanical characteristics, are determined. Based on the analysis of the signal, its shape, spectrum and fractal properties are found to be close enough to the shape, spectrum and fractal properties of the real vesicular breath sound. Представлена математическая модель для механизма генерации везикулярных звуков дыхания. В основу модели положено предположение о существенном вкладе в общий уровень звуков составляющих, которые связаны с колебаниями стенок альвеол в процессе дыхания. Стенки альвеол в легких моделируются как упругие мембраны. Показано, что при периодическом изменении натяжения возникают поперечные колебания, которые и являются источником звука в паренхиме. Предложена оценка характеристик композитного сигнала, который формируется за счет суперпозиции излучения ансамбля мембран различной геометрии и с различными механическими свойствами. Анализ характеристик модельного сигнала, таких как форма, спектр, фрактальная структура, дает достаточные основания для вывода об адекватном моделировании реальных везикулярных звуков. Представлено математичну модель для механізму генерації везикулярних звуків дихання. В основу моделі покладено припущення про суттєвий внесок у загальний рівень звуків складових, що пов'язані з коливаннями стінок альвеол у процесі дихання. Стінки альвеол у легенях моделюються як пружні мембрани. Показано, що при періодичній зміні натягу в мембрані виникають поперечні коливання, які і є джерелом звуку в паренхімі. Запропоновано оцінку характеристик композитного звукового сигналу, що формується за рахунок суперпозиції випромінювання ансамблю мембран різної геометрії та з різними механічними властивостями. Аналіз характеристик змодельованого сигналу, таких як форма, спектр, фрактальна структура, дає достатньо підстав для висновку про адекватне моделювання реальних везикулярних звуків дихання.